The Implementasi Regulasi Pemidanaan Terhadap Tindak Pidana Ringan Perspektif Restoratif Justice dan Tafsir QS. Al-Maidah: 33-34 : (Studi Putusan Nomor.247/PID.B/2009/PN.PWT Tentang Pencurian Kakao Oleh Nenek Minah) - Dina, Salma (As-Shahifah : Journal of Constitutional Law and Governance, 2024)
On August 2, 2009, in Darmakradenan Village, Ajibarang District, Banyumas, Central Java, Grandma Minah who was farming on her land which was also used as a cocoa plantation by PT RSA, took some cocoa fruits without permission. Grandma Minah's actions were later discovered by a plantation foreman who was on patrol. This research method uses a normative legal research method using the Case Approach which examines cases that occur in society and then examines them from the perspective of laws and regulations. The results of the study showed that there were weaknesses in the regulation of criminal penalties for minor crimes, as well as handling criminal acts using the conventional justice system or restorative justice in Grandma Minah's case and there was a view of Munir's Interpretation of QS Surat Al-Maidah verses 33 & 34 regarding criminal cases that Allah SWT allows them to turn it around before being arrested. However, if the repentance is sincere because of Allah SWT, not just a trick to avoid punishment, then the punishment is dropped.